The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/mco.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate, aging and brain health: the latest evidence

Abstract: Purpose of reviewWith an increasing population age, cognitive decline and age-associated neurodegenerative diseases are becoming increasingly prevalent and burdensome in society. Dietary supplementation with inorganic nitrate, which serves as a nitric oxide precursor, has been suggested as a potential nutritional strategy to improve brain health in older adults. In this review, we discuss recent findings in this area.Recent findingsA number of studies have emerged in the past 12–18 months exploring the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, with emerging evidence, a new perspective has begun to emerge which suggests that increased intake of nitrate may confer certain health benefits (4,8,9) . Indeed, it has now been demonstrated that consumption of dietary nitrate in the form of vegetables/vegetable-derived products can improve markers of cardiovascular (e.g., reduced blood pressure and improved endothelial function) (10)(11)(12)(13)(14) , brain (e.g., improved cognitive function and modulated cerebral blood flow) (15)(16)(17)(18)(19) , and oral (e.g., modified oral microbiome and increased resilience against oral acidification) health (20)(21)(22) . Similarly, nitrate has been shown to improve exercise capacity/performance across a range of population groups (23)(24)(25) , making it a popular ergogenic aid amongst athletes (3,26) .…”
Section: Introductionmentioning
confidence: 99%
“…However, with emerging evidence, a new perspective has begun to emerge which suggests that increased intake of nitrate may confer certain health benefits (4,8,9) . Indeed, it has now been demonstrated that consumption of dietary nitrate in the form of vegetables/vegetable-derived products can improve markers of cardiovascular (e.g., reduced blood pressure and improved endothelial function) (10)(11)(12)(13)(14) , brain (e.g., improved cognitive function and modulated cerebral blood flow) (15)(16)(17)(18)(19) , and oral (e.g., modified oral microbiome and increased resilience against oral acidification) health (20)(21)(22) . Similarly, nitrate has been shown to improve exercise capacity/performance across a range of population groups (23)(24)(25) , making it a popular ergogenic aid amongst athletes (3,26) .…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegenerative diseases elicit the progressive degeneration or death of neural cells, provoking either movement disorders, such as in ataxias, Amyotrophic Lateral Sclerosis (ALS) and Multiple Sclerosis (MS), or cognitive impairments (dementias), such as Alzheimer’s Disease (AD) and Parkinson’s Disease (PD). These are pathologies with increasing incidence in developed countries, accompanying a progressive aging of the population [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrite is further reduced to NO and exerts its biological activity after being swallowed into the GT [ 31 ]. Recent studies have described that DN supplementation can improve cognitive ability [ 21 , 32 , 33 ], skeletal muscle function [ 34 , 35 ], cardiovascular function [ 36 , 37 ] and other physiological functions closely related to human health [ 7 , 38 40 ], and provide some evidence that the bacteria with nitrate reductase are the intermediary of the potential mechanism [ 41 ]. One of the mechanisms by which these floras affect human health is their involvement in the production of the signaling molecule NO, which is involved in most physiological activities in the human body (e.g., participation in metabolism and maintenance of cardiovascular homeostasis, dilation of blood vessels, inhibition of atherosclerotic angiopathy, etc.).…”
Section: Introductionmentioning
confidence: 99%